Impact of Phospholipase C Gamma 2 Alzheimer's Disease Variants on Microglial Biology and Disease Pathogenesis. (20th December 2022) - Tsai, Andy Po‐Yi; Lin, Peter Bor‐Chian; Dong, Chuanpeng; Prisco, Gonzalo Viana Di; Wang, Nian; Bissel, Stephanie J; Oblak, Adrian L; Moutinho, Miguel; Liu, Yunlong; Atwood, Brady; Nho, Kwangsik; Lamb, Bruce T; et al.
Abstract: Background: Alzheimer's disease (AD) and other neurodegenerative diseases are typified by a robust microglial‐mediated immune response. Phospholipase C gamma 2 (PLCG2), whose variants confer altered risk for AD, is a critical signaling element for various immune receptors and is a key regulatory hub gene for immune signaling. A functional hypermorphic P522R variant (rs72824905) of PLCG2 has been identified to be protective against AD (OR= 0.68, p=5.83‐10). Significantly, we identified a novel SNP (rs617749044) associated with elevated AD risk (OR=1.164; p=0.047) encoding the PLCG2 M28L variant. Method: To investigate the impact of PLCG2 AD risk variants on microglial biology and disease pathogenesis, we have generated mice bearing either the M28L risk or the P522R protective PLCG2 variant, all crossed onto the 5XFAD amyloidogenic murine model of AD. Result: Here, we provide comprehensive analysis of PLCG2 action in mouse models of AD. We demonstrate that PLCG2 variants regulate protein‐protein interaction, alter microglial phenotypes in 5XFAD mice, regulate cytokine levels, drive distinct transcriptional phenotypes of microglia, and affect plaque pathology. Our data demonstrate that the M28L variant results in accelerated and exacerbated disease‐related pathology, and conversely, the P522R variant appeared to attenuate disease severity and progression. Conclusion: Together, our finding provides evidence that PLCG2 play an important role in AD pathophysiology, indicating PLCG2 as a potential new therapeutic target for AD.